Simultaneous Estimation of Pregabalin and Duloxetine, Used to Treat Nerve Pain, by Stability Indicating RP-HPLC Method Using the QBD Approach - Gosavi, Vaishnavi A.; Deshpande, Mahesh M.; Ghangale, Gauri D.; Chavan, Machindra J. (Current Pharmaceutical Analysis, 2024)
ObjectiveA novel stability indicating RP-HPLC method was developed and validated for the simultaneous estimation of Pregabalin and Duloxetine by using the QBD approach.MethodsTo determine the optimal parameters for the duloxetine and pregabalin study, we used Design Expert version 13.0 in this work. The mobile phase consisted of 0.8 ml/min of methanol: water (80:20, v/v) with o-phosphoric acid-adjusted pH 3.A 250 mm × 4.6 mm ID, 5 µm particle size Cosmosil C18 column was used. The UV-3000-M detector was used to detect at 218 nm.ResultsDuloxetine's retention time was 7.153 ± 0.1 min, whereas Pregabalin's was 4.481±0.1 min. The ICH parameters like linearity, accuracy, robustness, ruggedness, LOD and LOQ, and system suitability were determined. Likewise, the tailing factors were found to be 1.27 and 1.26, while the theoretical plates of duloxetine and pregabalin were found to be 8313 and 8549, respectively. The recovery study shows the results (99.37–99.84% for pregabalin and 99.03–99.74% for duloxetine), and the precision was obtained with a %RSD of less than 2%. The result of the assay was 99.92% for pregabalin and 99.39% for duloxetine. The developed method was used for the forced degradation study. The Box-Behnken design experiment using Design Expert 13.0 was adopted for the QBD approach.ConclusionAll the values obtained for different parameters were within the acceptable range of ICH. The developed method can be routinely used for the simultaneous estimation of Pregabalin and Duloxetine by using the QBD approach.
Keywords: Pregabalin